2022
DOI: 10.1007/s11356-022-22618-4
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of phosphorus recovery potential in sewage sludge incineration ashes — a case study

Abstract: A sewage sludge incineration ash contains large amounts of phosphorus, which are considered as a novel anthropogenic waste–based substitute for phosphorus natural resources. Phosphorus is accumulated at most in phosphate minerals of whitlockite structure, that contain Fe, Ca, and Mg and in the matrix composed of Si, Al, Fe, Ca, P, Mg, K, Na in various proportions. The goal of this study was to estimate phosphorus recovery potential. A four-stage sequential extraction, following the modified Golterman procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Additionally, Fe is characterized by low solubility especially in basic pH 40 . Kasina 21 indicated using sequential extraction method based on Golterman procedure 41 the total recovery of phosphorus of around 40–60%, which compared to other described in the literature ISSA was very low. The recovery rates from ISSA can reach up to 90% 42 depending on the ash composition.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, Fe is characterized by low solubility especially in basic pH 40 . Kasina 21 indicated using sequential extraction method based on Golterman procedure 41 the total recovery of phosphorus of around 40–60%, which compared to other described in the literature ISSA was very low. The recovery rates from ISSA can reach up to 90% 42 depending on the ash composition.…”
Section: Resultsmentioning
confidence: 87%
“…From the environmental point of view precipitation of sulphide minerals would be advantageous, since it is responsible for bonding and immobilization of metals considered as toxic 35 such as As, Zn, Cu, Cd and which presence may also negatively influence the phosphorus recovery 32 . From our previous study 21 , 36 we learned that the chelating Na-EDTA compound indicated low ability to extract phosphorus (at the level of only 35%), and the highest ability to extract heavy metals and potentially toxic elements (As, Zn, Mo) whereas the greatest release of phosphorus was obtained using sulphuric acid at the level of 64% however obtained fraction is considered non-bioavailable 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation